Modélisation des problématisations historiques en classe et chez les historiens - Sylvain Doussot (Recherches en Éducation)
Modelling reality is a key activity of any scientific inquiry. Modelling in didactics can play an intermediary role between school subject mater and its scientific reference. This is the way we intend to deal with modelling as in the problematization theoretical framework. One of the specificity of the modelling of problematizations lies in the fact that they hold together text of knowledge and text layout practices. There is however an inherent risk in modelling which is to ignore the historicity of the activity to be modelled. Such objectivist leeway would pay no attention to uncertainty attached to any social practice. This paper aims at puzzling out what it takes to manage this risk though the study of a course designed with the teacher about the French Revolution in end of primary school. It turns out that case study can be considered as a model for historical problematization at two different temporal levels.